2011
DOI: 10.2139/ssrn.1927110
|View full text |Cite
|
Sign up to set email alerts
|

The Financial Life Well-Lived: Psychological Benefits of Financial Planning

Abstract: As the financial planning industry undergoes a series of reforms aimed at increased professionalism and improved quality of advice, financial planner training in Australia and elsewhere has begun to acknowledge the importance of interdisciplinary knowledge bases in informing both curriculum design and professional practice (e.g. FPA 2009). This paper underscores the importance of the process of financial planning by providing a conceptual analysis of the six step financial planning process using key mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
(27 reference statements)
0
7
1
Order By: Relevance
“…In this study, the role of the financial planner was not found to influence retirement funding adequacy, which contradicts previous research that established a positive relationship between the role of the financial planner and retirement funding adequacy (Botha et al , 2014; Irving, 2012). As the study's sample comprised of black South Africans residing mainly in urban informal settlements and/or townships, this result can possibly be explained by the economic vulnerability of those residing in informal settlements and the limited accessibility to the services of a financial planner.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, the role of the financial planner was not found to influence retirement funding adequacy, which contradicts previous research that established a positive relationship between the role of the financial planner and retirement funding adequacy (Botha et al , 2014; Irving, 2012). As the study's sample comprised of black South Africans residing mainly in urban informal settlements and/or townships, this result can possibly be explained by the economic vulnerability of those residing in informal settlements and the limited accessibility to the services of a financial planner.…”
Section: Discussioncontrasting
confidence: 99%
“…First, Hanna and Lindamood (2010) argue that a financial plan helps people to feel more organized and to become more aware of their financial situation, both positively influencing financial satisfaction. Furthermore, people that are less financially knowledgeable often lack sense of control, which can be enhanced through PFA (Irving, 2012). Second, Winchester and Huston (2014) Fig.…”
Section: Paths 1 and 2: Pfa And Personal Factorsmentioning
confidence: 99%
“…Financial planning can be considered as a planning process in the financial realm and uses a series of mechanisms (Irving., 2012). In the context of the company financial planning is understood as the most important tool for companies to make financial decisions and achieve financial goals (Andres, 2014).…”
Section: Financial Planningmentioning
confidence: 99%